Observation of Cleft Palate in an Individual with SOX11 Mutation: Indication of a Role for SOX11 in Human Palatogenesis. (March 2018) - Khan, Umair; Study, DDD; Baker, Eleanor; Clayton-Smith, Jill
Objective: Point mutations and deletions within the SOX11 gene have recently been described in individuals with a rare variant of Coffin-Siris syndrome, OMIM 615866, an intellectual disability syndrome with associated features of nail hypoplasia, microcephaly, and characteristic facial features including a wide mouth and prominent lips. Participant: We describe a further patient with a mutation in SOX11 and phenotype resembling mild Coffin-Siris syndrome. Results: This boy had a cleft palate, a feature not previously seen in other patients with SOX11 mutations. Conclusion: We discuss This adds to the current evidence that SOX11 is a gene involved in palatogenesis.